STUDI KUALITATIF KESIAPAN IMPLEMENTASI KELAS RAWAT INAP STANDAR (KRIS) RUMAH SAKIT RSKD DADI PROVINSI SULAWESI SELATAN - Dewi Astuti (Public Health and Medicine Journal, 2026)
Background: The Standard Inpatient Class (SIC) in hospitals is a government- established regulation to standardize the quality of services and facilities for National Health Insurance (JKN) participants. This policy aims to reduce differences in quality between inpatient classes and ensure equal access to healthcare services. This study aimed to determine the readiness of Dadi Regional Special Hospital (RSKD), South Sulawesi Province, to implement the Standard Inpatient Class (SIC) policy established by the government through the BPJS Kesehatan (Social Security Agency). Research Method: This study used a qualitative approach with a phenomenological design, conducted through in-depth interviews with five key informants Sampel: the Head of the Planning Team, the Head of the Inpatient Installation, the BPJS Manager, the Head of Human Resources, and the Hospital Administration Manager.Research Results: The results indicate that Dadi Regional Special Hospital has generally allocated a budget of one billion rupiah to support the implementation of KRIS. In terms of human resources, the hospital has conducted optimal training and task allocation, although challenges remain in meeting the 12 KRIS standard criteria, particularly regarding bathroom facilities and the infrastructure of older buildings. Asset management has also begun to be directed toward meeting KRIS standards through inventory and room adjustments. Furthermore, the hospital's work plan has been developed in stages to support the comprehensive implementation of this policy.Conclusion: This study concludes that RSKD Dadi has demonstrated sufficient readiness to face the KRIS policy, although further improvements are still needed in several technical aspects and physical facilities. Kata kunci: Standard Inpatient Class (SIC), Hospital readiness, BPJS Kesehatan, Health policy, RSKD Dadi